Study on the utilization of patient care services of a General Hospital by diabetics. - Samarage, S.M (My University, 1992)
A descriptive cross sectional study was conducted in October 1992, with the objective of studying the utilization of patient care services of the general hospital Kalutara by diabetics, with a view to recommending measures to improve the patient care services. 13.9 per cent of the patients attending the medical clinic were diabetics.Very little patient education takes place at the clinic although adequate opportunities are available. The service providers themselves were not satisfied with the laboratory and dietary services of the hospital. The traditional approach of treating diabetics in hospital outpatients departments general medical clinics have proved to be inappropriate. There remains much unrealized potential for improving the care of the diabetic.This health systems research study unearthed such potential at the general hospital Kalutara.